CSC732 - Computer Graphics, Visualisation and Animation / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2018)
The course introduces the students to two-dimensional and three-dimensional aspects of computer graphics. It covers major topics in computer graphics modelling and rendering such as primitives drawing, viewing, object representation, rendering and illumination. Animation concepts are also introduced in this course.